LEGAL PRINCIPLES OF RURAL MEDICINE DEVELOPMENT IN THE CONTEXT OF MEDICAL REFORM IN UKRAINE - Yermolenko V.M.; Hafurova O.V.; Deineha M.A. (Scientific Journal of Pedagogy and Economics, 2020)
Legal support for the constitutional right of citizens to health care and medical care is an important condition for the realization of the principle of recognition the individual on the highest social value. The state guarantees everyone the right to protection of health, medical care and medical insurance; creates the conditions for effective and affordable medical care for all citizens. At the same time, the low level of provision of modern medical equipment, machinery and medicines makes it virtually impossible to provide timely and high-quality medical services in rural areas. The quality of primary health care in rural areas is in terrible condition and the people who live there, and this is more than 30 % of the total population of Ukraine, were very looking forward to changes in this area. After all, most of the old buildings and medical equipment are in poor condition. Medical institutions do not have a complete set of equipment, medical supplies and equipment necessary for primary care. The state of the legal regulation of providing medical care to the rural population of Ukraine objectively needs to be improved. Despite the adoption of numerous normative legal acts, the issues of providing health facilities located in rural areas with the necessary modern equipment and technology remained unresolved until recently. The goal of the article is to investigate the current problems of the legal support for providing medical care in the rural settlements. Particular attention is paid to the reform of the network of the rural health facilities and the problems of staffing. According to the results of the study it is established that from January 1, 2018, the implementation of the rural health reform began in Ukraine. This was due to the need to improve the availability of medical services for the population living in rural areas, to increase the efficiency and effectiveness of the use of funds allocated for the development of health care in the village, to bring the network of healthcare institutions in rural areas and their material and technical support into line with the needs of the population. Rural medicine reform is the lengthy process that requires not only careful adherence to legislation, but also a preliminary assessment of the real state of medicine in the remotest corners of Ukraine in order to prepare a platform for change. It is determined that the implementation of medical reform in cities is perceived better, and therefore much faster is happening, what not to say about the countryside. The prompt and timely solution of the problems of reforming rural medicine is possible with the assistance of the state authorities and local self-government, domestic businesses, foreign investors and financial donors, without which it is extremely difficult to cope with decentralization.